Serum Methotrexate Level Predicts Acute Kidney Injury After High-Dose Methotrexate: A Case Report and Single-Center Experience - Yen PW; Lin HY; Wu CC; Huang TC; Wu SJ; Pan SY; Hung KY (International Journal of Nephrology and Renovascular Disease)
Pao-Wen Yen,1 Hsing-Yu Lin,2 Chien-Chih Wu,2 Tai-Chung Huang,3 Shang-Ju Wu,3 Szu-Yu Pan,1,4 Kuan-Yu Hung1,5 1Division of Nephrology, Department of Internal Medicine, National Taiwan University Hospital, Taipei City, Taiwan; 2Department of Pharmacy, National Taiwan University Hospital, Taipei City, Taiwan; 3Division of Hematology, Department of Internal Medicine, National Taiwan University Hospital, Taipei City, Taiwan; 4Department of Integrated Diagnostics & Therapeutics, National Taiwan University Hospital, Taipei City, Taiwan; 5Graduate Institute of Clinical Medicine, College of Medicine, Taipei Medical University, Taipei, TaiwanCorrespondence: Chien-Chih Wu, Department of Pharmacy, National Taiwan University Hospital, Taipei City, Taiwan, Tel +886-2-23123456, Email r93451011@gmail.com Kuan-Yu Hung, Division of Nephrology, Department of Internal Medicine, National Taiwan University Hospital, Taipei City, Taiwan, Tel +886-2-23123456, Email kyhung@ntu.edu.twBackground: Acute kidney injury (AKI) is a serious complication following high-dose methotrexate (HD-MTX) treatment, despite established preventive measures. This study presents a case report and a retrospective review of patients treated with HD-MTX, aiming to identify risk factors for AKI and propose a modified treatment protocol.Methods: We report a case of a 43-year-old man with diffuse large B-cell lymphoma who developed severe AKI after HD-MTX therapy. Additionally, a retrospective review of 70 patients receiving HD-MTX at our institution was conducted to identify predictors of AKI. Serum methotrexate levels were analyzed to determine their significance in predicting AKI.Results: The index patient developed methotrexate intoxication and severe AKI despite receiving standard prophylactic measures, requiring temporary hemodialysis. The retrospective review identified serum methotrexate levels as a significant predictor of AKI (OR 11.84, 95% CI: 2.62– 53.53, p = 0.001). Higher initial serum methotrexate levels correlated with the development of AKI.Conclusion: Timely measurement of serum methotrexate levels is crucial in managing and preventing AKI in patients undergoing HD-MTX therapy. Based on our findings, we propose a modified HD-MTX treatment protocol to reduce the incidence of AKI. This includes earlier serum methotrexate level monitoring and adjustments in urine alkalization and leucovorin dosing strategies.Keywords: methotrexate, acute kidney injury